BENIGN BREAST LESIONS: DIAGNOSTIC VALUE OF MODERN IMAGING TECHNOLOGIES AND CLINICAL MANAGEMENT - A COMPREHENSIVE REVIEW - Michał Mazurek,; Karolina Ganczar,; Mikołaj Zalewski,; Marianna Rudzińska,; Stanisław Jurkowski,; Konrad Zieliński,; Łukasz Krzystek,; Jagoda Józefczyk,; Paweł Buć,; Karolina Buć, (International Journal of Innovative Technologies in Social Science, 2025)
Benign breast lesions comprise a wide spectrum of non-malignant proliferative, cystic, papillary, fibrotic, and inflammatory conditions that constitute the majority of abnormalities detected in breast imaging. Although inherently non-malignant, many of these lesions closely mimic malignancy on mammography, ultrasound, and MRI, presenting persistent diagnostic challenges in clinical practice. This review provides an integrated overview of the epidemiology, imaging characteristics, histopathologic features, and clinical management of the most common benign breast entities, including fibroadenoma, breast cyst, intraductal papilloma, sclerosing adenosis, fat necrosis, and radial scar.Each entity is discussed with emphasis on distinguishing imaging findings, risk associations, and the importance of radiologic-pathologic concordance in guiding management. While lesions such as fibroadenomas and simple cysts typically demonstrate benign imaging profiles and require minimal intervention, other lesions-including papillomas, radial scars, and sclerosing adenosis-are more complex due to their variable appearance and association with increased breast cancer risk. Conditions like fat necrosis and radial scars exemplify benign mimickers of malignancy, frequently resulting in false-positive imaging assessments and necessitating tissue sampling.A dedicated section highlights diagnostic pitfalls across imaging modalities and pathology, underscoring the value of multimodal assessment and careful evaluation of discordant findings. Collectively, this review reinforces the need for an individualized, correlation-driven diagnostic approach to ensure appropriate management, minimize unnecessary procedures, and maintain high diagnostic accuracy in contemporary breast imaging.